Tissue Engineering Approaches for Enamel, Dentin, and Pulp Regeneration: An Update - Geraldine M. Ahmed; Eman A. Abouauf; Nermeen AbuBakr; Christof E. Dörfer; Karim Fawzy El-Sayed (Stem Cells International)
Stem/progenitor cells are undifferentiated cells characterized by their exclusive ability for self-renewal and multilineage differentiation potential. In recent years, researchers and investigations explored the prospect of employing stem/progenitor cell therapy in regenerative medicine, especially stem/progenitor cells originating from the oral tissues. In this context, the regeneration of the lost dental tissues including enamel, dentin, and the dental pulp are pivotal targets for stem/progenitor cell therapy. The present review elaborates on the different sources of stem/progenitor cells and their potential clinical applications to regenerate enamel, dentin, and the dental pulpal tissues.